Exposure to particulate matter in different private commuting modes in Salem, India. Issue 1 (February 2021) - Ramesh Kumar, A; Jayabal, S; Ramkumar, P; Prabhakaran, J
Abstract: In our modern world, peoples are spending more time inside the vehicles in urban areas. This study assessed one of the critical pollutant of particulate matter PM10 (aerodynamic size ≤ 10 μm) in six private vehicles: hatchback car, sedan car, sports utility vehicle (SUV) car, multi utility vehicle (MUV) van, auto rickshaw, and motorcycle. PM pollutant in car and van transport modes evaluated under four different ventilation settings (air-conditioning (AC) ON/OFF; windows closed/open). In addition, air temperature (T) and relative humidity (RH) also assessed in six vehicles. The maximum PM exposure concentration was recorded in an auto-rickshaw, which is 4.28 times higher than the national pollution criteria. PM concentration lowered to 3.73, 1.94, and 1.53 timesin hatchback, sedan and SUV transport modes, respectively while altering ventilation condition from windows open to windows closed (AC ON) settings. There is no statistical significant difference (p > 0.05) between the transport modes of auto rickshaw-SUV, motorcycle-MUV, and motorcycle-sedan. All PM, T and RH parameters were correlated in car (AC ON) and auto-rickshaw transports.